New approaches to traditional learning – general aspects - Souza, Cacilda da Silva; Iglesias, Alessandro Giraldes; Pazin-Filho, Antonio (Medicina (Ribeirao Preto), 2014)
New challenges are needed in today’s educational settings and highly complex university curricula. To meet the social demands, changes in health professional education and new ways of working with knowledge of the educational institutions were required. In this article will be discussed: the advancement in different spheres, characteristics and barriers to break with the traditional structure and implementation of innovative teaching methodologies and learning. The institutional, the teacher and the student perspectives of this process will be discussed.